Boy Meets Girl: Say Hello to Courtship - Joshua Harris
Authored by the couple who penned the cautionary I Kissed Dating Goodbye, Boy Meets Girl offers help for teens seeking bible-guided counsel, not just pragmatic dating rules. Its guidance includes admonitions that young people think about the possibility of marriage while making dating decisions.